Kebijakan Penetapan Bitung Sebagai Kawasan Ekonomi Khusus (KEK) - Radityo Pramoda; Tenny Apriliani (Pusjar SKPP Lembaga Administrasi Negara, 2016)
The Bitung Special Economic Zone (SEZ) is a regional development policy specially devised to drive economic growth based on well-set-up infrastructures, and incentives. The role of central government in supervising the policy is very important in coping with each negative impact, both economic as well as social. The sole purpose of this qualitative research is to study the implementation of the regional development policy of Bitung as a Special Economic Zone. The analysis had been carried out with a case study approach, and then descriptively elaborated, and resulted in the finding of: (1) the previous development and infrastructure blueprint at the Bitung City level have so far been in line with the SEZ; (2) the SEZ has so far been attracting industry-based investment and creating work for the labors; (3) the formulated local regulations have been considered enough in giving legal security toward investment; (4) the establishment of Bitung as an SEZ has been considered as a sound strategic policy; and (5) the readiness of Bitung as an SEZ has been deemed adequate, despite the facts that it still needed minor adjustments in a few aspects, such as: better socialization, acceleration of land relinquishment, and increasing electricity/power.Keywords: Policy, Bitung Determination, Special Economic Zone (SEZ).Kawasan Ekonomi Khusus (KEK) Bitung merupakan kebijakan pengembangan wilayah dalam mendorong pertumbuhan ekonomi yang didukung infrastruktur berkualitas, serta pemberian kemudahan (insentif). Fungsi pemerintah pusat mengawal KEK Bitung, sangat penting untuk mencegah timbulnya dampak negatif secara ekonomi dan sosial. Penelitian kualitatif ini bertujuan untuk mengkaji implementasi pembangunan ekonomi dan penetapan kebijakan Bitung sebagai KEK. Analisis kajian dilakukan menggunakan pendekatan studi kasus, yang dipaparkan secara deskriptif. Hasil penelitian menunjukkan: (1) pembangunan yang telah ada maupun pengembangan rencana infrastruktur pada kawasan Kota Bitung sudah mendukung KEK; (2) KEK Bitung telah menciptakan investasi berbasis industri dan penyerapan tenaga kerja; (3) regulasi lokal yang dibentuk sudah memberikan kepastian hukum kepada investor; (4) Penetapan KEK Bitung merupakan kebijakan strategis pemerintah yang tepat; (5) kesiapan Bitung menjadi KEK secara umum sudah memadai, tetapi masih perlu untuk melaksanakan: sosialisasi kepada masyarakat, percepatan eksekusi pembebasan lahan, dan penambahan daya listrik.Kata kunci: Kebijakan, Penetapan Bitung, Kawasan Ekonomi Khusus (KEK).